Biomarkers of clinical severity in treated and untreated sickle cell disease: a comparison by genotypes of a single center cohort and African Americans in the NHANES study. (15th July 2021) - Njoku, Franklin; Zhang, Xu; Shah, Binal N.; Machado, Roberto F.; Han, Jin; Saraf, Santosh L.; Gordeuk, Victor R.
Summary: Haemolysis and vaso‐occlusion underlie multi‐organ system complications in sickle cell disease (SCD). We assessed real‐world biomarkers in University of Illinois adult SCD patients, categorised as severe (HbSS/Sβ 0 ‐thalassaemia; n  = 342) or mild (HbSC/Sβ + ‐thalassaemia; n  = 100) genotypes and stratified according to treatment. African‐American controls from the National Health and Nutrition Examination Survey (NHANES) were matched with each genotype category. Most measures of haemolysis, anaemia, inflammation and function of kidneys, liver and lungs differed markedly in untreated severe genotype patients compared to NHANES controls. These same biomarkers were significantly closer to the NHANES control range in untreated mild versus severe genotype patients, but they were not improved in severe genotype patients receiving treatment with hydroxycarbamide or blood transfusions, except that haemoglobin and HbF were higher with hydroxycarbamide. Systolic blood pressures did not differ among the SCD and NHANES groups, but diastolic pressures were higher in mild genotype patients. Ferritin in severe genotype patients on chronic transfusions was 50‐fold higher than NHANES controls. The cross‐sectional real‐world biomarkers of patients on hydroxycarbamide or transfusions were not markedly improved compared to untreated patients. This may be due partly to poor compliance or more severe disease. Our findings highlight the need for more effective treatments.